Peningkatan Kreativitas Mahasiswa dalam Pengolahan Sampah Anorganik Menjadi Kerajinan Kotak Tisu Ekonomis - Muhammad Juwantho Lewa; Rizal; Murninia; Yunisar Tri Rejeki; Hesti; Waode Safira Saputri; Ammel Indriawati; Anggun Saskia Dewi; Rahmad Bayu Efendi (SEWAGATI: Jurnal Pengabdian kepada Masyarakat, 2026)
Waste is one of the environmental problems that continues to grow alongside increasing consumer activity. Every day, people generate various types of waste, both organic and inorganic. One common example of inorganic waste is plastic and used cardboard, which take a long time to decompose naturally and thus have the potential to cause environmental pollution. Therefore, creative efforts are needed to reduce the amount of waste while increasing the utility of these used items. One possible solution is to repurpose cardboard waste into handmade crafts, such as tissue boxes, which offer both aesthetic and economic value. This activity was carried out on campus as part of a student learning practicum program, with student participants actively involved in the learning process—specifically in practice-based courses or community service activities. The activity took place in May 2026 and lasted approximately 3 days, covering stages ranging from observation and material collection to the product manufacturing process and evaluation of the activity’s outcomes. The method used was qualitative descriptive research with an experiential learning approach, involving students as active participants in the learning process. Data collection was conducted through participatory observation of the product-making process and interviews regarding technical challenges and opportunities for product development, and documentation of all stages of the activity. The data obtained were analyzed using data reduction, data presentation, and conclusion-drawing techniques. The results of the activity showed that repurpose cardboard waste into tissue boxes can enhance students’ creativity, increase their knowledge of waste management, and produce products with aesthetic value and potential market value.